Islamic Inscriptions in Ferghana and Zhetysu: Arabic-written monuments of the 11th–17th centuries from Kyrgyzstan (Russian), by Vladimir Nastich. - Simeon, Pierre (Journal of Islamic Archaeology, 2021)
Islamic Inscriptions in Ferghana and Zhetysu: Arabic-written monuments of the 11th–17th centuries from Kyrgyzstan (Russian), by Vladimir Nastich. Publishing House of Herzen State Pedagogical University of Russia, Saint Petersburg, 2019. 434pp. ISBN-13: 9785806426100.